2019
DOI: 10.1002/pen.25065
|View full text |Cite
|
Sign up to set email alerts
|

Simple approach to developing high‐efficiency neutron shielding composites

Abstract: Three distributions of boron nitride (BN) particles were designed: random, oriented, and periodic. The BN particles in multilayered high‐density polyethylene/boron nitride (HDPE/BN) composites were oriented along the extrusion direction and arranged regularly, and the BN/HDPE layers containing oriented BN particles exhibited periodic distribution in multilayered HDPE/(HDPE/BN) composites. Compared to the random distribution of BN particles, these structures could help reduce neutron transmittance and improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Comparing the single layer and multilayer PDMS composites, it is observed that the 5‐layer structure is associated with the highest AE, and it exhibits optimal shielding performance for x‐ray radiation, as it reaches approximately 89% attenuation rate under x‐ray radiations with 60 keV energy. This enhancement is the result of the synergistic attenuation effect of the polymer, nanofillers, and multilayer interfaces 44 …”
Section: Resultsmentioning
confidence: 99%
“…Comparing the single layer and multilayer PDMS composites, it is observed that the 5‐layer structure is associated with the highest AE, and it exhibits optimal shielding performance for x‐ray radiation, as it reaches approximately 89% attenuation rate under x‐ray radiations with 60 keV energy. This enhancement is the result of the synergistic attenuation effect of the polymer, nanofillers, and multilayer interfaces 44 …”
Section: Resultsmentioning
confidence: 99%
“…Despite the ability of the previously mentioned polymers to attenuate neutrons through elastic scattering, their shielding capabilities, especially those for thermal neutron shielding, could be further improved by introducing high‐neutron‐absorption‐cross‐section (σ abs ) compounds such as boron carbide (B 4 C), boron oxide (B 2 O 3 ), boron nitride (BN), and boric acid (H 3 BO 3 ) to the polymers. This modification would enable incident thermal neutrons to be attenuated using a far more efficient mechanism, namely neutron absorption, that results in less interactions and less materials being required to achieve sufficient attenuation 14,17–19 . An example of thermal neutron‐shielding material utilizing boron compounds as thermal neutron absorbers is the 80 phr B 2 O 3 /NR composites, which offered noticeably enhanced neutron‐shielding abilities compared to those of neat NR, as seen by the decrease in the neutron transmission percentage (I/I 0 ) from 98.2 ± 0.1% in the latter to just 57.9 ± 0.1% in the former (determined using samples with 2 mm thick) 19 …”
Section: Introductionmentioning
confidence: 99%
“…This modification would enable incident thermal neutrons to be attenuated using a far more efficient mechanism, namely neutron absorption, that results in less interactions and less materials being required to achieve sufficient attenuation. 14,[17][18][19] An example of thermal neutron-shielding material utilizing boron compounds as thermal neutron absorbers is the 80 phr B 2 O 3 /NR composites, which offered noticeably enhanced neutronshielding abilities compared to those of neat NR, as seen by the decrease in the neutron transmission percentage (I/I 0 ) from 98.2 ± 0.1% in the latter to just 57.9 ± 0.1% in the former (determined using samples with 2 mm thick). 19 In addition to boron compounds, rare-earth oxides, especially samarium oxide (Sm 2 O 3 ) and gadolinium oxide (Gd 2 O 3 ), have gained great attentions from researchers and product developers to replace conventional boron compounds because Sm and Gd offer much or Gd 2 O 3 (determined at a gamma energy of 0.5 MeV).…”
mentioning
confidence: 99%
“…Also, a Gd 2 O 3 based thermal neutron attenuating paint with an oxide mass fraction of 0.4 has been produced using commercial polyurethane and has shown good neutron protection properties [3]. In another example, nano-boron carbide (B 4 C) and boron nitride (BN) particle-reinforced polymer composites were developed for neutron shielding [4]. However, to increase the interfacial adhesion between BN and the polymer matrix, additional modification with coupling agents is needed [5], which might cause additional expenses.…”
Section: Introductionmentioning
confidence: 99%